The effect of heparin after primary percutaneous coronary intervention on short-term clinical outcomes in patients with ST-segment elevation myocardial infarction - Rouzbahani, Mohammed; Rezaie, Mohsen; Salehi, Nahid; Janjani, Parisa; Moghadam, Reza Heidari; Rai, Alireza; Montazeri, Nafiseh; Naderipour, Arsalan; Rad, Etrat Javadi; Asgari, Nader; Mahmoudi, Sousan; Motevaseli, Sayeh; et al. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Doing percutaneous coronary intervention (PCI) in the first hours of myocardial infraction (MI) is effective in re-establishment of blood flow. Anticoagulation treatment should be prescribed in patients undergoing PCI to decrease the side effects of ischemia. The aim of this study is to determine the effect of heparin prescription after PCI on short-term clinical outcomes in patients with ST-segment elevation myocardial infarction (STEMI). Materials: This randomized clinical trial study was conducted at Imam Ali cardiovascular center at Kermanshah university of medical science (KUMS), Iran. Between April 2019 to October 2019, 400 patients with STEMI which candidate to PCI were enrolled. Patients randomly divided in two groups: intervention group (received 5,000 units of heparin after PCI until first 24 hours, every 6 hours) and control group (did not receive heparin). Data were collected using a checklist developed based on the study's aims. Differences between groups were assessed using independent t-tests and chi-square (or Fisher exact tests). Result: Observed that, mean prothrombin time (PT) (13.30±1.60 vs. 12.21±1.15, p<0.001) and partial thromboplastin time (PTT) (35.30±3.08 vs. 34.41±3.01, p=0.003) were significantly higher in intervention group compared to control group. Thrombolysis in myocardial infarction (TIMI) flow grade 0/1 after primary PCI was significantly more frequently in control group (5.5% vs. 1.0%, p=0.034). The mean of ejection fraction (EF) after PCI (47.58±7.12 vs. 45.15±6.98, p<0.001) was significantly higher in intervention group. Intervention group had a statistically significant shorter length of hospital stay (4.71±1.03 vs. 6.12±1.10, p<0.001). There was higher incidence of re-vascularization (0% vs. 3.0%; p=0.013) and re-MI (0% vs. 2.5%; p=0.024) in the control group. Conclusion: Performing primary PCI with receiving heparin led to improve TIMI flow and consequently better EF. Receiving heparin is associated with lower risk of re-MI and re-vascularization.